APLIKASI OPTIMASI DINAMIS DENGAN PENDEKATAN MAXIMUM PRINCIPLE PADA PERTUMBUHAN EKONOMI DAERAH DAN ALOKASI PENDAPATAN BELANJA DAERAH - Supena, Yusup; yayan, Yayan (MATEMATIKA, 2002)
This papers derives a applied maximum principle for dynamic system regional development progam with continous lags, i.e. systems governed by integrodifferential equations. The result show that dynamic optimization technically is powerfull analysis to show optimization of government revenue practically.